2014
DOI: 10.1590/0001-3765201420130301
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol Effects on the P2 component of Auditory Evoked Potentials

Abstract: This is a second part of a research aimed to study the effects of alcohol on the electrophysiological processes in student volunteers. The first part showed that alcohol slowed the Omitted Stimulus Potential (OSP). This work studied the ethanol effects on the parameters (i.e. rate of rise, amplitude and peak latency) of the P2 component of the evoked potentials (EPs) yielded by trains of auditory stimuli. It is hypothesized here that if P2 and OSP waves share some common neural processes then alcohol should al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 37 publications
(44 reference statements)
0
4
0
1
Order By: Relevance
“…For each stimulus modality, separate linear regressions were used to test the relationship between parameters of the LLEP. 17 These regressions were calculated using the grand-average data for each parameter.…”
Section: Data Analysesmentioning
confidence: 99%
“…For each stimulus modality, separate linear regressions were used to test the relationship between parameters of the LLEP. 17 These regressions were calculated using the grand-average data for each parameter.…”
Section: Data Analysesmentioning
confidence: 99%
“…Two waves can also differ in amplitude and peak latency while having the same rise rate or differ in their rate of rise and amplitude but have the same latency (see Fig. 6 in Hernández et al 2014). Hernández and Vogel-Sprott (2010b) showed that acute alcohol can slow the OSP rise rate and latency but not its amplitude.…”
Section: Discussionmentioning
confidence: 99%
“…Hernández and Vogel-Sprott (2010b) showed that acute alcohol can slow the OSP rise rate and latency but not its amplitude. Later, Hernández et al (2014), who worked on the cognitive P200 wave, showed that the rate of rise resulted in more sensitivity to alcohol and more resistance to the habituation process compared to the latency and amplitude. The rate of rise was the only parameter modified by alcohol in the same fashion in both P200 and OSP.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[66,67]). Za pomocą CAEP próbuje się obiektywnie oceniać funkcjonowanie różnego rodzaju procesów poznawczych w chorobach związanych z nieprawidłowym działaniem ośrodkowego układu nerwowego, takich jak chociażby: epilepsja [68], udar mózgu [69], śpiączka [70], zespół alkoholowy [71], depresja, schizofrenia [66], choroba Alzheimera [72] czy chociażby różnego rodzaju formy demencji [73]. Naturalnym polem klinicznego wykorzystania słuchowych potencjałów korowych pozostaje jednak od lat przede wszystkim audiologia.…”
Section: Cel Pracyunclassified